Strategic Diversification as a Managerial Capability Under Persistent Market Volatility - Dewi Elviana Cahyaning C W (UDEX Institute, 2025)
Market volatility has evolved into a structurally embedded condition of contemporary business environments, destabilizing conventional assumptions about strategic planning, risk governance, and long-term value creation. Although diversification is widely regarded as a response to uncertainty, existing scholarship largely conceptualizes it as a structural configuration or portfolio allocation decision, thereby under-theorizing the managerial processes through which diversification is enacted and sustained. This conceptual paper advances a capability-based reconceptualization of strategic diversification, positioning it as a judgment-driven managerial capability rather than a static portfolio outcome. Drawing on strategic management, managerial cognition, and corporate governance perspectives, the study develops a process-oriented framework explaining how executives interpret volatility, balance strategic trade-offs, enforce governance discipline, and integrate diversified activities into a coherent strategic logic. The framework specifies four interdependent dimensions—cognitive framing, strategic balancing, governance orientation, and organizational integration—and identifies mechanisms through which diversification capability fosters strategic resilience, long-term value creation, and organizational coherence. By foregrounding managerial agency in governing strategic scope, this study extends diversification theory and offers a foundation for future research on organizational resilience under persistent uncertainty.